Internalizing Externalities through Payments for Environmental Services - Sudarsono Soedomo (Institut Pertanian Bogor (IPB University), 2012)
Forest ecosystems, including plantation forests, provide goods and services that are marketable and non-marketable. Positive externalities produced by forest ecosystems are rarely considered in pricing of marketable products that result in economic inefficiencies. Internalizing externalities is required to improve the economic efficiency. The traditional way to internalize an externality is by providing subsidies or imposing taxes. Recently, payments for environmental services are receiving more attention as an instrument for internalizing externalities provided by forest ecosystems. This promising alternative to improve our environment needs to be studied more extensively. In this paper, it can be indicated theoretically that the Pigovian tax, as a traditional way of addressing environmental problems, is able to mimic the result derived from the employment of environmental services payment. The difference is that environmental services payment improves the welfare of environmental service producers, whereas the Pigovian tax reduces it. A positive Pigovian tax increases the optimal rotation, which is positively associated with environmental improvement, but certainly reduces forest owner's welfare. This difference should be taken into account in the public policymaking so that perverse incentive may be avoided. Payment for environmental services as an additional income to forest growers, not as alternative source of income, is a potential tool to address simultaneously issues of environment and poverty that are frequently contested.